Inequalities in Educational Access in Mexico: A Study with Graduates Students of a High Performance Technical High School - Fernando Pérez-Santiago; Manuel Villarruel-Fuentes (Revista Electrónica Educare)
Access to the higher education system in Mexico has been characterized by educational inequalities explained by social and reproductionist currents. The phenomenon occurs in graduate students with a high school diploma and coming from different contexts (social, cultural, economic, institutional and academic ones) that create a process of transition far away from equal opportunities. Therefore, the differences due to cultural diversity do not generate equitable access to higher education institutions. The aim of this study was to identify the social, cultural and academic factors affecting the access to or the abandonment of the academic education of students with expectations of entering the higher education system. The research was based on the results obtained from forty technicians who studied at a vocational high school with high academic performance in Mexico, and were supposed to enter the higher level. It was an exploratory descriptive investigation with qualitative approach, using two multiple-choice item questionnaires whose results were analyzed interpretively. The sampling was non-probability, with the technique of “snowball” and “convenience”. The results showed that the level of parents’ schooling, social relations, and academic career of graduates were decisive to enter the higher education; so it can be concluded that the students’ origin generate inequality in educational achievement.